2012
DOI: 10.1016/s0972-6292(16)30458-2
|View full text |Cite
|
Sign up to set email alerts
|

Right Ventricular Pacing and Sensing Function in High Posterior Septal and Apical Lead Placement in Cardiac Resynchronization Therapy

Abstract: BackgroundThe conventional right ventricular (RV) lead position in cardiac resynchronization therapy pacemakers (CRT-P) is the RV apex (RV-A). Little is known about electrophysiological stability and associated complications of pacing leads in RV high posterior septal (RV-HS) position in CRT-P.MethodsTwo hundred and thirty-five consecutive CRT-P patients were included from 1999-2010. Pacing thresholds at 0.5ms and 2.5V, sensing electrograms and lead impedances were measured at implant and repeated 1,3,6,12,18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
(22 reference statements)
1
7
0
Order By: Relevance
“…compared septal and apical lead placement, and found that position in itself does not affect R wave amplitude or threshold significantly in patients with pacemakers [6], findings supported by Kristiansen et al. in the setting of CRT [5]. Thus, it seems the RV lead threshold changes observed in the DCM group in our study are likely disease, rather than lead–related.…”
Section: Discussionsupporting
confidence: 79%
“…compared septal and apical lead placement, and found that position in itself does not affect R wave amplitude or threshold significantly in patients with pacemakers [6], findings supported by Kristiansen et al. in the setting of CRT [5]. Thus, it seems the RV lead threshold changes observed in the DCM group in our study are likely disease, rather than lead–related.…”
Section: Discussionsupporting
confidence: 79%
“…The right ventricular apex is by far the most common pacing site, but active fixation steroid-eluting leads with a stable performance, low rate of dislodgement, and screwable design have made selecting pacing sites other than the right ventricular apex possible. Active fixation leads also provide the added convenience of possible lead extraction 9 10 . With an increasing number of pacemaker implantations and senior populations 11 , active-fixation pacing leads, have played a dominant role in Europe and the U.S.…”
mentioning
confidence: 99%
“…The authors have concluded on the basis of the literature data published so far that the QRS duration in RVOT stimulation is shorter than in RVA stimulation [8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Other authors also showed that QRS duration in the patients from the RVOT group was statistically significantly shorter than in the patients from the RVA group, but it had no protective effect on the left ventricular systolic function.…”
Section: Discussionmentioning
confidence: 99%